Health literacy research in Malaysia: a scoping review - Adina Abdullah,; Liew, Su May; Hani Syahida Salim,; Ng, Chirk Jenn; Karuthan Chinna, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Research on health literacy is expanding worldwide. Health literacy has been recognised as a critical determinant of health at the 2016 Shanghai Declaration. Little is known about health literacy research in Malaysia. This scoping review aims to identify and summarise published studies on health literacy in Malaysia. PubMed, Scopus and the Malaysian Medical Repository (MyMedR) databases were searched for published work by Malaysian researchers. Searches were conducted up to November 2019. The search terms used are related to ‘health literacy’ and ‘Malaysia’. Studies included were those involving Malaysian citizens and reporting on various aspects of health literacy. Studies were reviewed by two independent reviewers to determine their eligibility. Data extraction for the year of publication, name of authors, geographical location, research focus, and summary of findings from the full-text articles was carried out independently and any disagreement was resolved by consensus. A total of 29 articles were included with the earliest article published in 1985. Fifteen of the articles are on general health literacy, four on medication literacy, five on mental health literacy, three on media and e-health literacy and four on oral health literacy. Four articles are qualitative studies and the rest are quantitative studies. A few of the studies used validated health literacy tools such as Newest Vital Signs and HLS-EU-Q47. Therefore, we can conclude that there are only a limited number of articles published in the field of health literacy in Malaysia. Future work using validated international tools to allow comparison of the findings should be considered.